(untitled) - Goldstein, E. Brucez; E. Bruce Goldstein (Australia, 2007)
Helping you understand how you perceive what's around you-the wonder of seeing a face, hearing music, and smelling a rose-is what Goldstein's SENSATION AND PERCEPTION is all about. Writing clearly and using vivid full-color illustrations to clarify concepts, Goldstein shows you the importance of perception to your life. This textbook includes the latest breakthroughs in research and offers chapter-by-chapter correlation with online and multimedia resources that help you make the most of your study time. "Test Yourself" questions and "Think About It" exercises help you review and retain the material. The accompanying, "Virtual Lab" media exercises (available both on CD-ROM and online through the CengageNOW student tutorial platform) offer many animations and examples that clarify difficult concepts
Keywords: Senses and sensation; Perception